Air Pollution a Major Health Hazard In Future - Giridhar, P.; Neeraja, S. R. K. (Asian Journal of Pharmaceutical Research and Development, 2020)
Population, pollution and poverty are the major problems faced by the globe. These problems are interconnected with each other. Population is the major problem that leads to other problems. The population explosion along with urbanization and industrialization has greatly increased the intensity of environmental pollution. More than two million annual deaths and billions of cases of diseases are attributed to pollution. All over the world, people experience the negative effects of environmental degradation ecosystems decline, including water shortage, fisheries depletion, natural disasters due to deforestation and unsafe management and disposal of toxic and dangerous wastes and products. Indigenous peoples suffer directly from the degradation of the ecosystems that they rely upon for their livelihoods. Climate change is exacerbating many of these negative effects of environmental degradation on human health and wellbeing and is also causing new ones, including an increase in extreme weather events such as hot, cold spells of temperature or wet or dry spells of rainfall or cyclones or floods. Last year floods in States of Kerala and Karnataka were also attributed to climatic changes. Recent Delhi climatic conditions are also very alarming. The above facts clearly show the close link between the environment and the enjoyment of human rights, and justify an integrated approach to environment and human rights. The good practices were collected at the international, national and regional levels in collaboration through regional/sub-regional consultations as well as questionnaires and surveys Environmental factors must be favorable for the existence and development of living organisms. It is prime responsibility of human to protect, preserve and to sustain nature for the well being of every organism on this earth.